Complete mitochondrial genome of xanthid crab Atergatis floridus (Linnaeus, 1767). Issue 1 (2nd January 2018) - Karagozlu, Mustafa Zafer; Barbon, Michelle M.; Dinh, Thinh Do; Demayo, Cesar G.; Kim, Chang-Bae
Abstract: The complete mitochondrial genome sequenced from the floral egg crab Atergatis floridus (Linnaeus, 1767) and the determination of the position of the species in the reconstructed phylogenetic tree of the infraorder Brachyura using the protein coding mitochondrial genes are presented. Results show the mitochondrial genome length of A. floridus is 16, 435 bp with nucleotide distribution as 33.4% A, 20.3% C, 10.5% G and 35.8% T. The structure of the complete mitochondrial genome of the species is the same as with the previous xanthid record. The result of the phylogenetic analysis suggests that A. floridus is the closest species to other Xanthidae species in the brachyuran records. This is the first complete mitochondrial genome record from the genus Atergatis .